Diet Sustainability Analyses Can Be Improved With Updates to the Food Commodity Intake Database - Conrad, Zach; Cyril, Ashley; Kowalski, Corina; Jackson, Erin; Hendrickx, Brittany; Lan, Jessie Jie; McDowell, Acree; Salesses, Meredith; Love, David C.; Wiipongwii, Troy; Zhang, Fang Fang; Blackstone, Nicole Tichenor (Frontiers in Nutrition, 2022)
Diet sustainability analyses inform policymaking decisions and provide clinicians and consumers with evidence-based information to make dietary changes. In the United States, the Food Commodity Intake Database (FCID) provides a crosswalk for integrating nationally representative data on food intake from the National Health and Nutrition Examination Survey (NHANES) with data on sustainability outcomes from other publicly available databases. However, FCID has not been updated since 2010 and does not link with contemporary NHANES data, which limits further advancements in sustainability research. This study fills this research gap by establishing novel linkages between FCID and NHANES 2011-2018, comparing daily per capita food intake with and without these linkages, and making these data publicly available for use by other researchers. To update FCID, two investigators independently established novel data linkages, a third investigator resolved discrepancies, and a fourth investigator audited linkages for accuracy. Dietary data were acquired from nearly 45,000 adults from 2001-2018, and food intake was compared between updated vs non-updated FCID versions. Total food intake from 2011-2018 was 5-23% higher using the updated FCID compared to the non-updated version, and intake was over 100% higher in some years for some food categories including poultry, eggs, legumes, starchy vegetables, and tropical oils (P<0.001 for all comparisons). Further efforts may be needed to create new food composition data to reflect new products and reformulations that enter the food supply over time. This study removes a barrier to further diet sustainability analyses by establishing a data crosswalk between contemporary NHANES and other publicly available databases on agricultural resource use, environmental impacts, and consumer food expenditures.